Data-land use as a driver of soil fertility and biodiversity across an agricultural landscape in the central Peruvian Andes - de Valença, Anne W.; Vanek, Steven J.; Meza, Katherin; Ccanto, Raul; Olivera, Edgar; Scurrah, Maria; Lantinga, Egbert A.; Fonte, Steven J. (Colorado State University. Libraries, 2017)
Land use change and intensification in agricultural landscapes of the Andean highlands have resulted in widespread soil degradation and a loss in soil-based ecosystem services and biodiversity. This trend threatens the sustainability of farming communities in the Andes, with important implications for food security and biodiversity conservation throughout the region. Based on these challenges we sought to understand the impact of current and future land use practices on soil fertility and biodiversity, so as to inform landscape planning and management decisions for sustainable agroecosystem management. We worked with local communities to identify and map dominant land uses in an agricultural landscape surrounding Quilcas, Peru. These land uses existed within two elevations zones (low-medium, 3200-3800 m and high elevation, 3800-4300 m). They included three types of low-medium elevation forests (Eucalyptus, Alder and mixed/native species), five pasture management types (permanent pasture, temporal pasture (in fallow stage), degraded pasture, high-altitude permanent pasture and high-altitude temporal pasture (in fallow stage)) and six cropping systems (forage crops, maize/beans, and potato under four types of management). Soil fertility was evaluated in surface soils (0-20 cm) with soil physicochemical parameters (e.g., pH, soil organic matter, available nutrients, texture), while soil biological properties were assessed using the abundance and diversity of soil macrofauna and ground cover vegetation. Our results indicated clear impacts of land use on soil fertility and biological communities. Altitude demonstrated the strongest effect on soil physicochemical properties, but management systems within the low-mid elevation zone also showed important differences in soil biological communities. In general, the less-disturbed forest and pasture systems supported more diverse soil communities than the more intensively managed croplands. Degraded soils demonstrated the lowest overall soil fertility and abundance of soil macrofauna, but this may be reversible via the planting of Alder forests. Our findings also indicated significant covariation between soil physicochemical parameters, soil macrofauna and ground vegetation. This suggests that management for any one of these soil properties may yield unintended cascading effects throughout the soil subsystem. In summary, our findings suggest that shifts in land use across the landscape are likely to have important impacts on soil functioning and biodiversity.
Zip file includes readme file and data spreadsheet.
Department of Soil & Crop Sciences
Keywords: land use change; agricultural landscape; soil degradation; ecosystems; biodiversity; macrofauna; Andean highlands; soil fertility